The design of energy storage based on thermoelectric generator and bidirectional converter - Razman Ayop; Chee Wei Tan; Abba Lawan Bukar; Awang Jusoh; Nik Din Muhamad; Syed Norazizul Syed Nasir (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Energy storage plays an important role in the future of the power system. There are a lot of energy storage system (ESS) available and thermal energy storage shows a promising future. Conventionally, this system is based on a steam generator that converts heat energy to electrical energy and an electrical heater to convert electrical energy to heat energy. Nonetheless, there is still no proper ESS based on the thermoelectric generator (TEG), which can convert directly heat energy to electrical energy and vice versa. This paper proposed a power converter with a new controller for the thermal ESS based on the TEG. The bidirectional converter and the modified perturb and observe method are used to manage the energy transfer at the TEG. The thermal energy storage is based on the sensible approach, where the heat energy causes the temperature to increase. The results show that the thermal ESS based on the TEG is feasible since the energy can be stored and released from the proposed system.